2019
DOI: 10.1080/23802359.2019.1586468
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome sequence of a xerophilic fungus, Aspergillus pseudoglaucus

Abstract: Aspergillus pseudoglaucus is a xerophilic filamentous fungus which can produce various secondary metabolites. Here, we reported the complete mitochondrial genome sequence of A. pseudoglaucus isolated from Meju, a soybean brick in Korea. Its mitochondrial genome was successfully assembled from raw reads sequenced using MiSeq by Velvet and SOAPGapCloser. Total length of the mitochondrial genome is 53,882 bp, which is third longest among known Aspergillus mitochondrial genomes and encoded 58 genes (30 protein-cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Number of tRNAs in this mitochondrial genome is smaller than the other fungal mitochondrial genomes missing three types of tRNAs: tRNA-Ala, tRNA-Gln, and tRNA-Tyr. Thirteen out of 32 PCGs are identified as endonuclease, which is one of the contributors to expand Aspergillus and Penicillium mitochondrial genomes (Joardar et al 2012;Park et al 2019).…”
mentioning
confidence: 99%
“…Number of tRNAs in this mitochondrial genome is smaller than the other fungal mitochondrial genomes missing three types of tRNAs: tRNA-Ala, tRNA-Gln, and tRNA-Tyr. Thirteen out of 32 PCGs are identified as endonuclease, which is one of the contributors to expand Aspergillus and Penicillium mitochondrial genomes (Joardar et al 2012;Park et al 2019).…”
mentioning
confidence: 99%
“…Sequence alignments of ten conserved genes from twelve Aspergillus and one Penicillium mitogenomes (Juh asz et al 2008;Futagami et al 2011;Sun et al 2011;Joardar et al 2012;Zhao et al 2012;Park, Kwon, Huang, et al 2019;Park, Kwon, Zhu, Mageswari, Heo, Kim, et al 2019) including that of Afla-Guard V R and one Podospora mitochondrial genome (Cummings et al 1990) as an outgroup were calculated by MAFFT 7.450 (Katoh and Standley 2013) and concatenated. The neighbour-joining (10,000 bootstrap repeats) and maximum-likelihood (1,000 bootstrap repeats) phylogenetic trees were constructed using MEGA X (Kumar et al 2018).…”
mentioning
confidence: 99%
“…Interestingly, length of Ophiocordyceps sinensis mitochondrial genome is much larger than that of Fusarium mangifere but both were clustered in one clade with high bootstrap values (Figure 2(A)). The mitochondrial genome expansion in Aspergillus genus [16][17][18][19] and variable size of Fusarium mitochondrial genomes [18,20,21] suggested that mitochondrial genome expansion events may be occurred several times during evolution of fungal species. In addition, tree displayed two distinct clades in Colletotrichum genus, which is congruent with previous phylogenetic study [22] ( Figure 2).…”
Section: Koreanmentioning
confidence: 99%